Silica diagenesis promotes early primary hydrocarbon migration - Abu-Mahfouz, I; Cartwright, J; Idiz, E; Hooker, J; Robinson, S (Geological Society of America, 2020)
We present evidence that hydrocarbon source rocks can be preconditioned for primary hydrocarbon migration at an early stage of catagenesis by pore-scale processes linked to silica diagenesis. The evidence comes from a detailed petrographic and geochemical study of the Jordan Oil Shale (JOS), an immature to early mature Upper Cretaceous to Paleogene source rock developed on the platform regions of Jordan. Diagenesis of biogenic silica led to silicification of the source rock interval and the growth of chert nodules. Localization of bitumen veins in reaction rims around these nodules is used to argue that silica diagenesis promotes the early mobilization of hydrocarbons from the geochemically identical, disseminated bitumen within the host mudstones. We propose a model in which early-formed bitumen migrated into neo21 forming Mode 1 fractures that formed as a result of the crystallization pressure imposed from the growing chert nodule. Hydraulic fracturing occurred under elevated bitumen fluid pressures that approached lithostatic stress values under burial depths of the order of 1000 m. The recognition that silica diagenesis can promote the early migration of neo-forming bitumen raises the possibility that primary hydrocarbon migration may occur earlier and at shallower depths than predicted by solely kinetic modelling approaches wherever silica diagenetic reactions are coeval with catagenesis.